Synthesis of Heavy-Atom-Free Triplet Photosensitizers Based on Organoboron Complexes - Koli, Mrunesh; Mula, Soumyaditya (Synlett, 2023)
A new class of organoboron complexes have been developed as heavy-atom-free triplet photosensitizers. A methodology was developed for the synthesis of an indolocarbazole–imine boron diﬂuoride (IIBD) dye and its dimer from a 6-formylindolocarbazole. The IIBD dye was then coupled with a BODIPY dye through the C-2 or C-8 position of the latter to synthesize two dyads. Both dyads showed superior photophysical properties to those of the IIBD dyes. The relative triplet conversion efficiencies of these dyes were determined by measuring their singlet-oxygen (1O2) generation capacities. All the synthesized dyes showed high 1O2 generation compared with the BODIPY dye PM567. The dyad linked through the C-2 position of the BODIPY core showed the highest 1O2 generation efficiency, which could be useful for photodynamic therapy of cancers.
Keywords: indolocarbazoles; dye; organoboron compounds; BODIPY dyes; triplet photosensitizers; photocatalysts